Gate-all-around nanowire FET sensors with ultrahigh sensitivity and low noise - Pushpapraj Singh (2012)
In this research work, new kinds of field-effect transistor (FET)-based sensing elements were developed to maximize the detection limits of conventional piezoresistors. These sensing elements were able to enhance the piezoresistive sensitivity and reduce the intrinsic noise, which significantly improved the detection limits and make them adaptable for lower strain detection applications.